Improving Mastery of Science Concepts Using Problem Based Learning Models in Class V in Elementary School - M. Habib Ridho; Ramdhan Witarsa; Musnar Indra Daulay; Nurhaswinda Nurhaswinda; Putri Hana Pebriana (Edumaspul: Jurnal Pendidikan, 2022)
The background of this study is the low mastery of science concepts by fifth grade students at SDN 008 Salo Timur. This study aims to improve the mastery of science concepts using the problem-based learning model for class V in elementary schools. This research is a class follow-up research, which was carried out in two cycles and each cycle consisted of two meetings. The subjects in this study consisted of 1 teacher and 29 students, while the object was to use a problem-based learning model to improve students' mastery of science concepts. The research instrument consisted of teacher activity observation sheets and student activity observation sheets, test sheets and documentation sheets during the learning process using the problem based learning model. While the data analysis technique used is descriptive qualitative and quantitative analysis. Based on the results of research that has been carried out through 2 cycles, at the second meeting of cycle I mastery of classical mastery of science concepts students only 24.13% in the low category and the average learning value is only 67.03 in the medium category. It is known that there was an increase in students' mastery of science concepts after improvements were made in the second cycle of meeting 2, the classical mastery of students' science concepts was 86.20% in the very high category and the average student learning score was 80.55 in the high category. Based on the results of the study, it can be concluded that if the problem-based learning model is used , it can improve students' mastery of science concepts in class V 008 Salo Timur. Keywords: Mastery of Science Concepts, problem based learning (PBL)